Advance in Heterologous Expression of Biomass-Degrading Auxiliary Activity 10 Family of Lytic Polysaccharide Monooxygenases - Hongyu Zhang; Zixuan Zhou; Tingting Lou; Rong Xiang; Deguang Zhang; Danyun Wang; Suying Wang (Fermentation, 2023)
AA10 family lytic polysaccharide monooxygenases (AA10 LPMOs) are mainly distributed in bacteria. Because of their characteristics of oxidative degradation of crystalline polysaccharides, such as cellulose and chitin, they have great application potential in industrial biomass conversion and have attracted wide attention. Efficient heterologous expression of LPMOs by recombinant engineering bacteria has become the main strategy for the industrial production of enzymes. The research progress of AA10 LPMOs’ heterologous expression systems was reviewed in this paper. The construction strategies of its diversified heterologous expression system were introduced based on the design and processing of the expression host, vector, and LPMOs gene. The effects of different expression systems on the soluble expression of LPMOs and the development direction of the construction of LPMOs’ heterologous expression systems were discussed. The broad application prospect of LPMOs in the biomass conversion and biofuel industry has been prospected.